Binary black hole mergers from merged stars in the Galactic field - Stegmann, Jakob; Antonini, Fabio; Schneider, Fabian; Tiwari, Vaibhav; Chattopadhyay, Debatri (Physical review, 2022)
The majority of massive stars are found in close binaries which: (i) are prone to merge and (ii) are accompanied by another distant tertiary star (triples). Here, we study the evolution of the stellar postmerger binaries composed of the merger product and the tertiary companion. We find that postmerger binaries originating from compact stellar triples with outer semimajor axes aout,init≲101-102 AU provide a new way to form binary black hole mergers in the galactic field. By means of a population synthesis, we estimate their contribution to the total black hole merger rate to be R(z=0)=0.3-25.2 Gpc−3 yr−1. Merging binary black holes that form from stellar postmerger binaries have exceptionally low mass ratios. We identify a critical mass ratio q≃0.5 below which they dominate the total black hole merger rate in the field. We show that after including their additional contribution, the mass ratio distribution of binary black hole mergers in the galactic field scenario is in better agreement with that inferred from gravitational wave detections.
Gesehen am 28.08.2022